Faktor-faktor yang berhubungan dengan kejadian diabetes mellitus tipe-II pada pasien rawat jalan - Cut Cahaya Rani; Nunung Sri Mulyani (Politeknik Kesehatan Kemenkes Aceh, 2021)
Background: Diabetes Mellitus (DM) occurs due to hyperglycemia, abnormalities in carbohydrate, protein, and fat metabolism caused by decreased insulin secretion, or decreased insulin sensitivity or both, causing chronic microvascular, macrovascular, and neuropathic complications. Aceh ranks 8th in the prevalence of diabetes mellitus from all provinces in Indonesia at 2.6% and the national prevalence is 2.1%.Objective: This study aims to determine the factors associated with the incidence of type-II diabetes mellitus in outpatients.Methods: An analytical observational study with a cross-sectional design was conducted in 2019 in Banda Aceh. The sampling method is purposive sampling with a total of 96 samples, outpatients at the Meuraxa Hospital. Data collection that has been carried out includes data on age, gender, genetics, obesity, and diet. Chi-square test data analysis at 95% CI.Results: The results of this study have shown that people who are over 43 years of age suffer from type-II diabetes mellitus and people who are obese, have genetics, and have poor diet can suffer from type-II diabetes mellitus. There was a significant relationship between age, genetics, obesity, and diet with the incidence of type-II diabetes mellitus (p < 0.05), while gender did not have a significant relationship with the incidence of diabetes mellitus (p > 0.05).Conclusion: Obesity in patients with type II diabetes is age, genetic factors, and diet. Suggestion, it is necessary to continue counseling related to the causes of type-II diabetes mellitus in patients who visit the hospital.